Manners and Styles of Violating the Administration's Duty to Implement the Administrative Judiciary - Najem, Jenan; Qadori, Tagreed (Journal of Legal Sciences, 2023)
The forms and styles used by the administration in order to violate the implementation of administrative provisions are among the most dangerous steps that the administration pursues to evade the obligation to implement them , which is helped by the fact that it is not possible to limit the images that vary and increase continuously with the development of functional relations in the administrative field, which makes it difficult to have a legal codification of these images and methods of confronting them.The administration is aware of this and seeks to achieve its objective of non-implementation with its superior capabilities and wide powers to make these images legal behaviors that the judiciary is unable to confront. The occurrence of changes in it by a legal text, and the judiciary pays attention to focusing on these forms and methods that the administration follows in order to guarantee the rights of individuals that are guaranteed by constitutional texts in various countries of the world.